2023
DOI: 10.3389/fmed.2022.1076372
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin in preeclampsia: A meta-analysis and systematic review

Abstract: ObjectiveTo review of the efficacy and safety of pravastatin use for prophylaxis and treatment of preeclampsia.DesignSystematic review and meta-analysis of clinical studies evaluating pravastatin for treatment and/or prophylaxis of preeclampsia.Data collectionTwo independent reviewers systematically searched data from PubMed, Scopus, Web of Science, Cochrane, Embase, and clinicaltrials.gov databases, for studies evaluating pravastatin for prevention of pre-eclampsia.ResultsFourteen studies were identified, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…30 Further, certain statins have been tested to treat hypertensive disorders during pregnancy. 31 In addition, women have tended to report more adverse effects ascribed to statin. 24,32 Prior studies have hypothesized this could be due to differential exposure to public warnings affecting patients’ perceptions as well as possible drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…30 Further, certain statins have been tested to treat hypertensive disorders during pregnancy. 31 In addition, women have tended to report more adverse effects ascribed to statin. 24,32 Prior studies have hypothesized this could be due to differential exposure to public warnings affecting patients’ perceptions as well as possible drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group’s earlier meta-analysis highlighted that pravastatin therapy started before the 20th gestational week reduces preeclampsia development. The therapy is also beneficial for neonates, as it reduces the number of neonates born with IUGR, neonatal admissions to intensive care units, and the occurrence of preterm deliveries ( 102 ).…”
Section: Commentmentioning
confidence: 99%
“…Additionally, limited drug concentrations were observed in the umbilical cord, supporting the notion of restricted transplacental transfer of pravastatin. Lefkou et al demonstrated that in women with antiphospholipid syndrome and preeclampsia or intrauterine growth restriction (IUGR), the administration of 20 mg of pravastatin led to improved pregnancy outcomes and fetal health [59][60][61]. Furthermore, the efficacy of high-dose intravenous immunoglobulin therapy for pregnant women with aspirin-heparin-resistant secondary antiphospholipid syndrome was also evaluated [62].…”
Section: Treatment Options In Apsmentioning
confidence: 99%